POLA ASUH PANTI SOSIAL DI KOTA PEKANBARU (STUDI KASUS PANTI SOSIAL PENGASUH ANAK) - Ziana Syafira; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Orphanage is a social institution that does not have unable parents and families to shape the development and behavior of better children. The purpose of this research is to know the pattern of caring in Child Care Institution and know the program of guidance activities conducted in the orphanage. This research used qualitative method with descriptive approach, trying to describe how caring pattern in Child Care Institution of Pekanbaru. Techniques of data collection are used through interviews, observation, and documentation. Data analyst techniques include data reduction, data presentation and conclusion and verification. The result of the research shows that the parenting pattern used by the Caregivers is a democratic and authoritarian parenting style. Patterns for toddlers and children aged 6-17 years are different. Toddlers are cared for by a nanny and children aged 6-17 are cared for by ustadz and ustadzah. The program of guidance activities in Child Care Institution are two programs that are long term and short term program. Caregivers provide for the child's physical and psychic needs. Keywords: Pattern of Foster, Activity Development Program